Kajian produktivitas modal pada usaha penangkapan ikan yang menggunakan alat tangkap bagan apung dengan ukuran berbeda di Desa Lamontoli Kabupaten Morowali - Arsad; La Ola, La Onu; Arami, Hasnia; Abdullah; Sriwulan, Desy (Jurnal Sosial Ekonomi Perikanan, 2023)
This study aimed to determine the total costs, total revenues, profits, and productivity of the large size (18×18×15) m3 and small size (13×13×10) m3 of floating lift net in Lamontoli Village, South Bungku District, Morowali Regency. This research was conducted from January to February 2022. The sampling technique was carried out by census on eight fishermen of floating lift net. The data collections in this study were observation, interviews, and documentation. Data analysis were consisted of analysis of total costs, total revenues, profits, and capital productivity. The results of the study showed that the total cost of large floating lift net was IDR 2,843,967/trip and small floating lift net which was IDR 1,751,472/trip. The amount of total revenue for large floating lift net was IDR 10,823,750/trip and the small floating lift net was IDR 7,612,500/trip. The profits for large floating lift net was IDR 8,042,972 and small floating lift net was IDR 5,861,028/trip. The business productivity value of large floating lift net was 3.93 and the business productivity value obtained by small floating lift net was 4,48.